Tolerance-like mediated suppression by mesenchymal stem cells in patients with dust mite allergy–induced asthma - Kapoor, Simi; Patel, Shyam A.; Kartan, Saritha; Axelrod, David; Capitle, Eugenio; Rameshwar, Pranela (Journal of allergy and clinical immunology, 2012)
Mesenchymal stem cells (MSCs) can suppress and enhance immune functions. MSCs show promise as off-the-shelf cellular therapy for several disorders, including inflammation. We investigated the effects of MSCs on the proliferation of PBMCs to allergic subjects (dust mite [DM]), allergic asthmatic subjects, or both. Proliferation was studied by using tritiated thymidine uptake with or without MSCs. The refractoriness of PBMCs to DM was examined after preconditioning with MSCs and after repeated challenge with low-dose DM. Flow cytometry was used to study regulatory T cells and dendritic cells (DCs), and ELISA was used to study cytokine production. Seven subjects with allergic asthma met the inclusion/exclusion criteria. MSCs significantly (P < .05) reduced the proliferation of 6 subjects with allergic asthma but not those with allergy alone. The effect was specific to the allergen because MSCs did not affect challenges to tetanus toxoid. There was no change in CD4/CD25/forkhead box protein 3–positive cells, although there were decreased IFN-γ and increased IL-10 levels. Numbers of mature DCs were increased 6-fold. Refractoriness to DM was achieved by means of repeated exposure to low-dose DM and MSCs and also MSC- preconditioned MSC. MSCs suppressed the proliferation of DM-challenged PBMCs from allergic asthmatic subjects but not from allergic subjects without asthma. MSCs blunted the maturation of DCs but not regulatory T cells. Repeated exposure to low-dose DM and MSCs, as well as preconditioning of PBMCs with MSCs, caused refractoriness to DM. These findings have implications for the use of MSCs in attenuation of the inflammatory responses to allergic triggers in asthmatic patients with off-the-shelf MSCs.